2013
DOI: 10.1167/iovs.13-11681
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Permeability Transition Pore in Inflammatory Apoptosis of Human Conjunctival Epithelial Cells and T Cells: Effect of Cyclosporin A

Abstract: RESULTS. In IOBA-NHC, TNFa, and IFNc induced MPTP opening, DWm loss, and increased cell apoptosis. This was accompanied by upregulation of Fas/FasL; Bax; and caspase-3, -8, and -9 activation. Addition of CsA prevented IOBA-NHC from cell death by blocking MPTP opening, DWm loss, Fas/FasL, and caspase activation. In PMA/aCD3-activated Jurkat T cells, MPTP opening and DWm loss were increased along with cell apoptosis and upregulated Fas/FasL/ caspase expressions. CsA further promoted T-cell apoptosis, DWm loss, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 44 publications
5
41
0
Order By: Relevance
“…Furthermore, a transient 'flickering' mode of mPTP opening has also been described in the literature playing a role in ROS-mediated signaling and adaptive cellular stress responses. 41,42 A cyclosporin A-insensitive ionomycin-induced pore opening was also found in our cell system, similar to what was described in other types of cells, 43 which could indicate alternative mitochondrial membrane permeabilization mechanisms. Ionomycin-induced mPTP opening also appeared to be dependent on differentiation state: the more undifferentiated cells (Glu-P19SCs) presented the highest resistance to pore induction.…”
supporting
confidence: 88%
“…Furthermore, a transient 'flickering' mode of mPTP opening has also been described in the literature playing a role in ROS-mediated signaling and adaptive cellular stress responses. 41,42 A cyclosporin A-insensitive ionomycin-induced pore opening was also found in our cell system, similar to what was described in other types of cells, 43 which could indicate alternative mitochondrial membrane permeabilization mechanisms. Ionomycin-induced mPTP opening also appeared to be dependent on differentiation state: the more undifferentiated cells (Glu-P19SCs) presented the highest resistance to pore induction.…”
supporting
confidence: 88%
“…The loss of mitochondrial membrane potential is an indication of irreversible cell injury, which induces cell apoptosis (Gao et al 2013). We found that the mitochondrial membrane potential decreased and the apoptosis rate increased in NaF-treated Sertoli cells, and there was a significant doseresponse relationship between NaF and MMP, similar results also appeared on the relationship between NaF and apoptosis rate.…”
Section: Discussionsupporting
confidence: 68%
“…Studies have demonstrated that collapse of the mitochondrial membrane potential due to opening of the MPT pore typically triggers apoptosis (Qanungo et al, 2005;Gao et al, 2013;Ramkumar et al, 2013). The loss of mitochondrial membrane potential in MP3-treated cells supports the observed cytotoxic activity of the fraction in the MTT assay.…”
Section: Discussionmentioning
confidence: 52%